Reflection Vectors and Quantum Cohomology of Blowups - Milanov, Todor; Xia, Xiaokun (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
Let be a smooth projective variety with a semisimple quantum cohomology. It is known that the blowup Blₚₜ() of at one point also has semisimple quantum cohomology. In particular, the monodromy group of the quantum cohomology of Blₚₜ() is a reflectiongroup. We found explicit formulas for certain generators of the monodromy group of the quantum cohomology of Blpt() depending only on the geometry of the exceptional divisor.